Bibliometric Study of Publications on Eruption of Deciduous and Permanent Teeth - Barbara Alves da Fonseca; Thaís de Oliveira Fernandes; Leonardo Santos Antunes; Lívia Azeredo Alves Antunes (Association of Support to Oral Health Research (APESB), 2024)
Objective: To perform a bibliometric analysis on deciduous and permanent eruption publications to discuss the global trends and prospects on the topic. Material and Methods: A systematic search was conducted on the Scopus database. The characteristics of the publications, including co-cited authors, organizations, countries, most cited sources, publications, and keyword co-occurrence, were analyzed using VOSviewer software version 1.6.18. Results: After applying exclusion criteria, 492 studies were included in the analysis. The majority of research centers were located in Europe. "Archives of Oral Biology" emerged as the most frequently cited journal. The United States and Brazil were the most frequently cited countries in the publications. Notable co-authors included Kuchler E. C. and Hägg U. The most frequently cited keywords were associated with oral pathologies, tooth development, odontogenesis, and genetics. The most recent papers were published in journals focused on oral diseases. Conclusion: This bibliometric analysis highlights that the future of research in this field is likely to be focused on the investigation of tooth eruption in both deciduous and permanent teeth, with an emphasis on genetics, tooth development, timing of tooth eruption, and syndromic conditions. While well-accepted in the fields of Pediatrics and Orthodontics, there is a growing interest in this topic within oral biology and pathology journals in the Americas, with the United States and Brazil leading in terms of publications and citations.